THE EFFECT OF PROFITABILITY AND TAX MINIMIZATION ON TRANSFER PRICINGMODERATED BY FIRM SIZE (AN EMPIRICAL STUDY ON MINING COMPANIES - Yeni Tata Rini; Ahmad Dahlan; Azhari Atul Aini (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to examine the effect of profitability and tax minimization on transfer pricing, with firm size serving as a moderating variable, in mining companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2022 period. The research employed a quantitative approach using secondary data obtained from the audited annual financial statements of mining companies listed on the IDX. The sample consisted of 12 companies (36 firm-year observations) selected through purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM), including descriptive statistics, measurement model evaluation, structural model assessment, and hypothesis testing. The results indicate that profitability has a significant negative effect on transfer pricing, while tax minimization has no significant effect on transfer pricing. Firm size has a significant negative direct effect on transfer pricing and significantly moderates the relationship between profitability and transfer pricing. However, firm size does not moderate the relationship between tax minimization and transfer pricing. The coefficient of determination (R²) shows that profitability, tax minimization, and firm size explain 36.6% of the variation in transfer pricing. In conclusion, transfer pricing practices in Indonesian mining companies are primarily influenced by profitability and firm size, whereas tax minimization does not significantly affect transfer pricing, either directly or through the moderating role of firm size. Keywords: Firm Size, Profitability, Tax Minimization, Transfer Pricing